Precariatization of the Preschool Teachers' Workforce and Its Consequences on the Well-Being and in-School Relations - Toprak, Ziya; TORAN, MEHMET (IOS Press, 2025)
Background: With the augmentation of flexible capitalism, episodic, short-term work has been a common workforce regime in distinct fields and sectors, including education. Increasingly teachers are forced to work short-term, leading to lower-wages and insecurity. T & uuml;rkiye, which had employed teachers permanently, changed its teacher workforce regime in 2005; introducing contract-based and short-term employing to the regime.Objective: The aim of this study was to investigate the consequences of the new workforce regime on teachers' overall well-being and relationships with their peers.Method: The present study utilized in-depth interviews with 16 preschool teachers, who had different employing status; paid, fixed-term contracted and permanent teachers, which allowed to compare these groups. A theoretical thematic analysis for data analysis was conducted, utilizing MAXQD.Results: Findings revealed that the paid and fixed-term groups experienced financial insecurity, future hopelessness, bullying and discrimination in school, all of which resulted in lowered overall well-being while paid teachers reporting higher levels and permanent teachers not reporting such issues but enjoying their jobs.Conclusion: The current Turkish teacher employment regime has resulted in a school environment that was detrimental to school relations and well-being of teachers. The results implied that permanent teachers were enjoying a relatively comfortable and safe zone, fixed-term teachers were confined to ambiguity and temporality, and precarious teachers postponed their life to an unknown and unimaginable future. Therefore, policy makers should consider immediate and far-reaching consequences of precariat while making workforce policies. The study suggested the termination of precarious work in schools effective immediately.
Keywords: Early Childhood Education; Early Childhood Teachers; Employment Regime; Precarious Work; Well-being; Workforce; Workplace Relations